Inovações tecnológicas do concreto: análise do cenário atual e expectativas da construção civil - Carvalho, Vitor Mendes de [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The construction industry is constantly evolving, developing new techniques and materials in order to optimize the work of professionals, benefit consumers and generate economic benefits. In the case of concrete, which is omnipresent in construction works, it is natural that this material is the focus of research aimed at improving its properties. This paper aimed to present some technological innovations of concrete developed in the international market, such as concrete canvas, biological concrete, air purifying concrete and translucent concrete and analyze the needs to meet the standards and expectations of the Brazilian construction industry. In this regard, it is necessary that each concrete innovation be evaluated for the desired structural or non-structural function, so that it meets the different rules governing this material in the Brazilian market. In addition to the need to comply with the standards, it was found that these innovations still have a high cost and incompatible with the Brazilian market that, in some cases, reach values seven times higher than the traditional concrete used in the national construction market.

A indústria da construção civil está sempre se reinventando, desenvolvendo novas técnicas e materiais, com o intuito de otimizar o trabalho dos profissionais do setor, beneficiar os consumidores e gerar benefícios econômicos. No caso do concreto, que é onipresente nas obras de construção civil, é natural que esse material seja foco de pesquisas, que visem melhorar suas propriedades. Este trabalho teve como objetivo apresentar algumas inovações tecnológicas do concreto desenvolvidas no mercado internacional, como a lona de concreto, o bioconcreto, o concreto purificador de ar e o concreto translúcido e analisar questões relacionadas às necessidades de atendimento às normas e as expectativas do setor de construção civil brasileiro. Neste aspecto, é necessário que cada inovação do concreto seja avaliada para a função estrutural ou não estrutural desejada, para que atenda as diferentes normas que regem este material no mercado brasileiro. Além da necessidade de atendimento às normas, constatou-se que estas inovações ainda possuem um custo elevado e incompatível com o mercado brasileiro que, em alguns casos, chegam a valores sete vezes superior ao do concreto tradicional, utilizado no mercado da construção civil nacional.
Concrete technological innovations: analysis of the current scenario and expectations of civil construction
Keywords: Building materials; Innovations in construction; Bioconcrete; Concrete canvas; Light-transmitting concrete; Concrete pavement with TiO2; Materiais de construção civil; Inovações na construção; Bioconcreto; Lona de concreto; Concreto purificador de ar; Concreto translúcido; Materiais de construção; Concreto; Construção civil